Keterlibatan Suami Dalam Perawatan Pasca Persalinan - Mastina, Mastina; Karo, Dina Andriani Br; Eliani, Risda (-, 2026)
The World Health Organization (WHO 2015) has emphasized the urgency of male involvement during the perinatal period to support accessibility of services for women and promote positive participation of men in their roles as partners and fathers. The purpose of the study was to implement and evaluate Husband Involvement in Postpartum Care to prevent complications during postpartum. The design of this community service activity used the technique of providing material to the mother's partner, and pre- and post-tests were given to the mother's partner. The results of the study showed an increase in maternal knowledge about breast care in postpartum mothers with an average value of 87.78.